Anxiety of Pregnant Women Facing Childbirth In Busungbiu District, Buleleng - Hesteria Friska Armynia Subratha; Ketut Espana Giri; Ni Komang Sulyastini; Made Bayu Oka Widiarta (Sean Institute, 2023)
Numerous studies have consistently demonstrated the association between stress, depression, and heightened anxiety during pregnancy, which can lead to adverse outcomes such as low birth weight (LBW), preterm birth, and developmental issues in infants. Recent data from the Buleleng District Health Office in December 2021 revealed that approximately 3.1% of infants in the region had low birth weights. Notably, the prevalence of LBW in the catchment area of the Busungbiu I Public Health Center in Buleleng exceeds the district average of 5.6%. Against this backdrop, the present study conducted at the Busungbiu I Public Health Center aims to explore the concerns of pregnant women regarding childbirth amidst the ongoing COVID-19 epidemic. Employing a descriptive-quantitative research design, the study focused on pregnant women who had attended prenatal check-ups at the Busungbiu I Public Health Center within the previous month. The sample comprised 80 respondents selected through probability random sampling. Among the respondents, the highest proportion, accounting for 35%, reported experiencing moderate levels of anxiety. Furthermore, analysis based on the respondents' age groups revealed that the youngest participants exhibited the highest levels of moderate anxiety. Additionally, respondents who had completed elementary school or an equivalent level of education, as well as those with junior high school education or its equivalent, comprised the groups with the highest prevalence of moderate anxiety. Based on the findings, it is recommended to implement targeted initiatives aimed at enhancing pregnant women's understanding of the significance of pregnancy education. Furthermore, it is encouraged to intensify efforts in providing comprehensive support to pregnant mothers, ensuring they are equipped with the necessary knowledge and resources to navigate the challenges associated with pregnancy and childbirth effectively.